Evidence of COVID-19 pandemic influence on well-being produced by urban gardening: a before-after study - Tuominen, Laura S.; Helanterä, Heikki; Karell, Patrik; Rapeli, Lauri; Vuorisalo, Timo; Brommer, Jon E. (Springer Nature, 2025)
The COVID-19 pandemic showed us that maintaining and increasing individual and community resilience is essential, particularly in cities. Access to urban green spaces such as parks and gardens supports resilience and well-being. Here, we studied how the pandemic influenced the attitudes towards and outcomes of urban box gardening in the city of Turku in Finland. We analyzed this small-scale social-ecological system before and during the pandemic in 2019, 2020, and 2021. We find that box gardening’s importance increased for many gardeners due to the pandemic, supporting that box gardening can enhance resilience. We find that gardeners remain motivated to cultivate but contrary to expectations, they report receiving fewer benefits, suggesting the pandemic’s negative influence on well-being extends to urban gardening. Our findings highlight the manifold and long-term influence of disturbances. The long-term changes in attitudes and outcomes suggest that the pandemic’s influence on urban gardening might be even transformative.